Turbulence of second sound waves in superfluid He II - Brazhnikov, M.Yu.; Efimov, V.B.; Kolmakov, G.V.; Levchenko, A.A.; Lebedeva, E.V.; Mezhov-Deglin, L.P. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
We communicate the results of numerical studies of acoustic turbulence in a system of slightlydissipating, nonlinear second sound waves in superfluid He II. It is shown that at sufficiently high amplitude of the external driving force the power-like energy distribution over frequency is formed in the system of second sound waves. This distribution is attributed to formation of the acoustic turbulence regime in the system. The interval of frequencies in which the distribution has a power-like form is expanded to high frequencies with increasing the amplitude of the driving force. The distribution of the energy inside this interval is close to Ew ~ w2. It is shown that the distribution of energy Ew depends on the value of the nonlinearity coefficient of the second sound, but does not depend on the sign of the coefficient, i.e., the coherent structures (shock waves) donot contribute to the statistical properties of the turbulent state.